2022
DOI: 10.3390/molecules27123849
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Uses, Phytochemical Analysis, and Anti-Inflammatory Properties of Australian Tropical Medicinal Plants

Abstract: Australian tropical plants have been a rich source of food (bush food) and medicine to the first Australians (Aboriginal people), who are believed to have lived for more than 50,000 years. Plants such as spreading sneezeweed (Centipeda minima), goat’s foot (Ipomoea pes-caprae), and hop bush (Dodonaea viscosa and D. polyandra) are a few popular Aboriginal medicinal plants. Thus far, more than 900 medicinal plants have been recorded in the tropical region alone, and many of them are associated with diverse ethno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 309 publications
2
9
0
Order By: Relevance
“…After that, total phenolic content (TPC) and total flavonoid content (TFC) both were calculated for the ethanol extract to obtain the quantitative phytochemical analysis which indicated the antioxidant potential of D. viscosa . Similar results of the phytochemical analysis were observed in a few other studies ( Hossain, 2019 ; Yeshi et al, 2022 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…After that, total phenolic content (TPC) and total flavonoid content (TFC) both were calculated for the ethanol extract to obtain the quantitative phytochemical analysis which indicated the antioxidant potential of D. viscosa . Similar results of the phytochemical analysis were observed in a few other studies ( Hossain, 2019 ; Yeshi et al, 2022 ).…”
Section: Discussionsupporting
confidence: 90%
“…After that, total phenolic content (TPC) and total flavonoid content (TFC) both were calculated for the ethanol extract to obtain the quantitative phytochemical analysis which indicated the antioxidant potential of D. viscosa. Similar results of the phytochemical analysis were observed in a few other studies (Hossain, 2019;Yeshi et al, 2022). The antioxidant potential of D. viscosa leaves (ethanol extract) was evaluated by two methods including 1) 1, 1-Diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging activity and 2) Ferric Reducing Antioxidant Power (FRAP) assay.…”
Section: Figuresupporting
confidence: 75%
“…The results of previous reports have elucidated the relationship between medicinal plants and the NFκB pathway. Ginger, Zingiber officinale , is among the studied plants, and was approved as an alternative anti-inflammatory agent against the production of cyclooxygenase (COX)-2 and nitric oxide (NO) [ 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to our obtained data, the crude ginger extract, 6-gingerol, and 6-gingerol formulated into nanocarriers have shown that they can accelerate the wound-healing process. This activity may be due to the strong relationship between reductions in the biosynthesis of pro-inflammatory markers and enhancements in the wound-healing process [ 33 ]. Acute and chronic wounds occur after any disruption in skin integrity, either in the epidermis or dermis layers.…”
Section: Discussionmentioning
confidence: 99%
“…Tropical countries have abundant medicinal plant resources which have yet to be discovered [10][11][12]. Te binahong (Anredera cordifolia) is a plant native to tropical and subtropical South American countries and later brought to Southeast Asia.…”
Section: Introductionmentioning
confidence: 99%